2020
DOI: 10.1021/acsnano.9b09264
|View full text |Cite
|
Sign up to set email alerts
|

Cells Undergo Major Changes in the Quantity of Cytoplasmic Organelles after Uptake of Gold Nanoparticles with Biologically Relevant Surface Coatings

Abstract: Here, we use cryo soft X-ray tomography (cryo-SXT), which delivers 3D ultrastructural volumes of intact cells without chemical fixation or staining, to gain insight about nanoparticle uptake for nanomedicine. We initially used dendritic polyglycerol sulfate (dPGS) with potential diagnostic and therapeutic applications in inflammation. Although dPGS-coated gold nanoparticle (dPGS-AuNP) uptake followed a conventional endocytic/degradative pathway in human lung epithelial cell lines (A549), with cryo-SXT, we dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 85 publications
3
42
0
Order By: Relevance
“…An increase in number of mitochondria is associated with the use of stored cellular energy reserves in response to nutrient deprivation or exercise [ 67 ]. Thus, the intensive stress caused by N-SNPs may cause an increase in the number of mitochondria in cells, in order to generate more energy and avoid this stress [ 68 ]. Moreover, the dose-dependent increase in number of peroxisomes observed in all tested cells after exposure to N-SNPs may indicate that N-SNPs kill cancer cells via inducing oxidative stress, as ROS can be generated in peroxisomes by the production of H 2 O 2 during fatty acid oxidation [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in number of mitochondria is associated with the use of stored cellular energy reserves in response to nutrient deprivation or exercise [ 67 ]. Thus, the intensive stress caused by N-SNPs may cause an increase in the number of mitochondria in cells, in order to generate more energy and avoid this stress [ 68 ]. Moreover, the dose-dependent increase in number of peroxisomes observed in all tested cells after exposure to N-SNPs may indicate that N-SNPs kill cancer cells via inducing oxidative stress, as ROS can be generated in peroxisomes by the production of H 2 O 2 during fatty acid oxidation [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Free Cy5 and Cy5 loaded NPs without membrane coating (Cy5-N) and Cy5 loaded membrane coated NPs (Cy5-MN) (each containing the same content of Cy5) were added into the medium of BMDM and Caco-2 cells with the final concentration of Cy5 as 10 μg/mL and the concentration of NPs as 0.19 mg/mL. The internalization of free Cy5 and Cy5 loaded NPs was determined by flow cytometry in 4 hours and 24 hours, respectively according to the previous studies 30 , 31 and the mean fluorescence intensity was statistically analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…143 Also, it was found that Au-NPs increase number of mitochondria and decrease the number of lipid droplets indicating that cells produce more energy in trial to remove the stress caused by NPs. 142 Furthermore, the high incidence of, autophagic vacuoles, endosomes, cytoplasmic vacuoles were observed after treatment cancer cells with Ag-NPs. 142,144 Another study showed that Ag-NPs and copper NPs resulted in increasing lipid droplets that may be return to nanotoxicity that impaired the lipid catabolic activity.…”
Section: Killing Strategies Of Nps Against Living Cellsmentioning
confidence: 98%
“…142 Furthermore, the high incidence of, autophagic vacuoles, endosomes, cytoplasmic vacuoles were observed after treatment cancer cells with Ag-NPs. 142,144 Another study showed that Ag-NPs and copper NPs resulted in increasing lipid droplets that may be return to nanotoxicity that impaired the lipid catabolic activity. The authors reported also that high incidence of peroxisomes as well as lysosomes and low distribution of endoplasmic reticulum indicating necrosis.…”
Section: Killing Strategies Of Nps Against Living Cellsmentioning
confidence: 98%
See 1 more Smart Citation